Copper line Pre-Qualification Assessment for High-Speed Broadband in Malaysia - Hashim, Nabihah; Md Yusoff, Nelidya; Amrin, Astuty; Asrokin, Azhari; Zainal Abidin, Ahmadun Nijar (Journal of Advanced Research in Applied Mechanics, 2020)
The copper access-network operators face the challenge of developing and maintaining the cost-effective digital subscriber line (DSL) services that are competitive to other broadband access technologies. The copper line quality assessment process is crucial to ensure the customers enjoy their speed subscription. Through this process, service providers can evaluate the capability of copper lines before deploying the broadband service. Furthermore, for the unstable condition of copper lines, the root cause of the problems can be identifying earlier, which helps the operators to do preventive action and avoid offering the service to customers using that copper lines. This paper discusses the proposed prequalification assessment method and the impact of every proposed stage. This proposed assessment showed that the speed performance would be dropped more than 50% if the impairments exit in the copper line. Thus, any service providers can avoid serving high-speed broadband to subscribers using the unstable cable condition. Through this preventive process, it will benefit the service providers.